The Effect ofGuava Leaf(Psidium guajava L.)Solution With Different Doses on Degree ofFertilityAnd Hatchability of Green Catfish (Hemibagrus nemurus) - Lili Yuspita Daulay; Hamdan Alawi; Nuraini Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The study was conducted on March-April 2019, at the Hatchery and Breeding Laboratory at the Fisheries and Marine Science Faculty, University of Riau, Pekanbaru. The purpose of the study was to determine the effect of guavaleaf (Psidium guajava L.)solutionwith different doses on degree of thefertilizationand hatching rateof greencatfish(Hemibagrus nemurus).This experiment used Completely Random ized Design (CRD)with four treatments and three replications. The dose of guava leaf solution used was P1 (0 g/L), P2 (0,6 g /L), P3 (0,7 g/L) and P4 (0,8 g /L). Theimmerse green catfish eggs in guava leaf solution for 4 minutes with a density of ± 170 eeg (0,2 g) and incubated in an aquarium. Larvae wererearing in aquarium at stocking density 4 larvae/L for 10 day. The results showed that the dose of guava leaf solution gave a very real effect to eeg fertilization rate (89,21%), egg hatching rate (84,58%) and survival rate (88,33)of larvae. The best dose guava leaf solution to increase fertility, egg hatchability and survival rate of larvae was 0,7 g/L. Keywords : Hemibagrus nemurus, Eeg Fertility, Eeg Hatchability, Guava Leaf